Chloroplast Vesiculation and Induced Chloroplast Vesiculation and Senescence‐Associated Gene 12 Expression During Tomato Flower Pedicel Abscission - Magda Tušek Žnidarič; Maja Zagorščak; Živa Ramšak; Katja Stare; Marko Chersicola; Maruša Pompe Novak; Aleš Kladnik; Marina Dermastia (Plant Direct)
ABSTRACT Abscission is a tightly regulated process in which plants shed unnecessary, infected, damaged, or aging organs, as well as ripe fruits, through predetermined abscission zones in response to developmental, hormonal, and environmental signals. Despite its importance, the underlying mechanisms remain incompletely understood. This study highlights the deleterious effects of abscission on chloroplast ultrastructure in the cells of the tomato flower pedicel abscission zone, revealing spatiotemporal differential gene expression and key transcriptional networks involved in chloroplast vesiculation during abscission. Significant changes in chloroplast structure and vesicle formation were observed 8 and 14 h after abscission induction, coinciding with the differential expression of vesiculation‐related genes, particularly with upregulation of Senescence‐Associated Gene 12 (SAG12) and Chloroplast Vesiculation (CV). This suggests a possible vesicle transport of chloroplast degrading material for recycling by autophagy‐independent senescence‐associated vacuoles (SAVs) and CV‐containing vesicles (CCVs). Ethylene signaling appears to be involved in the regulation of these processes, as treatment with a competitive inhibitor of ethylene action, 1‐methylcyclopropene, delayed vesiculation, reduced the expression of SAG12, and increased expression of Curvature Thylakoid 1A (CURT1A). In addition, chloroplast vesiculation during abscission was associated with differential expression of photosynthesis‐related genes, particularly those involved in light reactions, underscoring the possible functional impact of the observed structural changes. This work provides new insights into the molecular and ultrastructural mechanisms underlying abscission and offers potential new targets for agricultural or biotechnological applications.